Green synthesis, antibacterial activity and computational study of pyrazoline and pyrimidine derivatives from 3-(3,4-dimethoxy-phenyl-1-(2,5-dimethyl-thiophen-3-yl)-propenone - Khan, Salman Ahmad; Asiri, Abdullah Mohamed; Kumar, Sanjay; Sharma, Kamlesh (European Journal of Chemistry, 2014)
Various pyrazoline and pyrimidine derivatives were synthesized by the reaction of thiosemicarbazide / phenyl hydrazine / hydrazine hydtate / thiourea / urea with 3-(3,4-dimethoxy-phenyl-1-(2,5-dimethyl-thiophen-3-yl)-propenone under microwave irradiation, which itself was derived from the reaction of 3-acetyl-2,5-dimethylthiophene with 3,4-dimethoxy benzaldehyde. The corresponding pyrazoline and pyrimidine derivatives were obtained in good to excellent yields. All of the new compounds obtained were characterized by IR, 1H NMR, 13C NMR, MS and elemental analyses. The anti-bacterial activity of these compounds were tested in-vitro by the disk diffusion assay against two Gram-positive and two Gram-negative bacteria. The results showed that one of the pyrazoline derivatives is better at inhibiting the growth as compared to chloramphenicol against both types of the bacteria (Gram-positive and Gram-negative). Furthermore, all the molecules were subjected to computational calculation using the density functional theory with B3LYP method to corroborate their antibacterial activities.